Estradiol Attenuates the Severity of Primary Toxoplasma gondii Infection-Induced Adverse Pregnancy Outcomes Through the Regulation of Tregs in a Dose-Dependent Manner - Qiu, Jingfan; Zhang, Rong; Xie, Yanci; Wang, Lijuan; Ge, Ke; Chen, Hao; Liu, Xinjian; Wu, Jiangping; Wang, Yong (Frontiers in Immunology, 2018)
Estradiol (E2) plays a crucial and intricate role during pregnancy to mediate several aspects of the pregnancy process. A perplexing phenomenon in congenital toxoplasmosis is that the severity of Toxoplasma gondii (T. gondii)-mediated adverse pregnancy outcome is closely related with time of primary maternal infection during pregnancy. In this study, the results showed that T. gondii infection in early pregnancy was more likely to induce miscarriage in mice than in late pregnancy, which may be related to inflammation of the maternal-fetal interface. Meanwhile, the T. gondii infection induced-apoptotic rate of Tregs was higher and the expression of programmed death-1 (PD-1) on Tregs was lower in early pregnancy than in late pregnancy. As the level of E2 in mouse serum gradually increased with the development of pregnancy, we proposed that E2 may contribute to the discrepancy of Tregs at different stages of pregnancy. Thus, we investigated in vitro and in vivo effects of E2 in regulating Tregs. We found that E2 in vitro could protect Tregs against apoptosis and up-regulate the expression of PD-1 on Tregs in a dose-dependent manner through ERα. Likewise, the simulated mid-pregnancy level of E2 in nonpregnant mice also alleviated the T. gondii infection-induced apoptosis of Tregs and potentiated the PD-1 expression on Tregs. Therefore, in the patho¬genesis of T. gondii-induced abnormal pregnancy, E2 helped maintain the immune balance and improve the pregnancy outcome through regulating Tregs. This finding illustrates the intricate working of hormone-immune system interaction in infection-induced abnormal pregnancy.